The Effect of Sorbitol Concentration on The Characterictics of Purple Yam Starch (Dioscorea alata) Based Edible Film: Yam starch based edible film - Sari, Rani Permata; Ulyarti, Ulyarti; Rahmi, Silvi Leila (PUI BiGME Universitas Jambi, 2022)
Edible film is a thin layer made of edible material, used as a food surface coating that serves to inhibit the migration of moisture, oxygen, carbon dioxide, aroma, and lipids. This research used yam starch (Dioscorea alata) as the main ingredient in the production of edible film and sorbitol as plasticizer. The aim of the research was to determine the effect of sorbitol at different concentration on the characteristic of yam starch-based edible film. Sorbitol was applied at different concentration (w/w): 0.67%, 0.80%, 0.93%, 1.07%, 1.20% and 4 replications. Sorbitol concentration was found to be a significant factor affecting the value of water vapor transmission rate and sweetness, but not a significant factor for thickness, transparency, brightness and solubility of edible film. The concentration of sorbitol 0.67 is preferred for edible film with 0.15mm thickness, transparency 11.87%/mm, compressive strength 52.150%, solubility 9.60%, water vapor transmission rate 18.1608g/m2h and brightness 59.525.